Dietary Indian frankincense (Boswellia serrata) ameliorates murine allergic asthma through modulation of the gut microbiome. (October 2022) - Suther, Cassandra; Devon, Liv; Daddi, Lauren; Matson, Adam; Panier, Hunter; Yuan, Hanshu; Saar, Katarzyna; Bokoliya, Suresh; Dorsett, Yair; Sela, David A.; Beigelman, Avraham; Bacharier, Leonard B.; et al.
Graphical abstract: Highlights: Mice given an oral supplement of Boswellia serrate had suppressed asthma symptoms. Treated mice had significant increases of Bifidobacterium in their guts. The Bifidobacterium was further identified as B. pseudolongum . Oral administration of isolated B. pseudolongum alleviated airway inflammation. Abstract: Asthma is associated with significant morbidity. The gut microbiome has been shown to effect asthma development and exacerbation. In this study, we tested an oral supplement containing Boswellia serrata (Indian frankincense) tree resin on allergic pulmonary inflammation and gut microbiome. An OVA based allergic airway model was used and mice were orally gavaged 100 mg/kg of Boswellia serrata as a supplementation throughout asthma sensitization and challenge. Treated mice showed significant weight loss, lower total lung leukocytes, eosinophil and Th2 cytokines, improved histology scoring and reduced reactivity to methacholine challenge. Asthmatic mice without Boswellia serrata supplementation showed a decrease in overall bacterial diversity, while treated mice were protected against loss. Boswellia serrata treated mice had a significant increase in Bifidobacterium, which was identified as Bifidobacterium pseudolongum. Oral administration of B. pseudolongum also reduced airway inflammation, suggesting Boswellia serrata may work as an anti-asthma agent via increases in B. pseudolongum from prebiotic influences.